Fertilizer schedule for yield of fresh fluted pumpkin (Telfairia occidentalis) grown in lower Benue river basin of Nigeria - Obiagwu, C J; Odiaka, N I (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1991 and 1992 cropping seasons to determine appropriate schedule of N, P and K for growth and development of fluted pumpkin (Telfailia occidentalis Hook. f.) in acid sandy soil. Vine number, length of vines, girth and fresh-matter yield were measured at 2-week intervals after fertilizer application. P alone at 22 kg/ha gave the highest fresh-matter yield (5.04 kg/plant), followed by 22 kg P/ha +42 kg K/ha (4.98 kg/plant) and SO kgNlha+22 kg P/ha (4.89 kg/plant). These yields wereÂ significantly different (P = 0.05) from treatments and combinations without P. NPK applied in 2 splits (4 and 8 weeks after germination) gave fresh-matter yield of 5.45 kg/plant compared with 4.16 kg/plant produced by single application of NPK or 4.76 kg/plant given by 3 splits of NPK. Fresh-matter yields obtained from band or broadcast application (6.4 and 6.3 kg/plant respectively) were significantly different (P= 0.05) from ring application or point placement methods (4.7 and 4.4 kg/plant respectively). Band application of NPK therefore proved a superior method of fertilizing fluted pumpkin.